Rare combination and transcatheter treatment during single session in an infant: Patent ductus arteriosus and major aortopulmonary collateral artery concordance - Osman Güvenç; Ender Ödemiş; Murat Saygı; İbrahim Halil Demir (KARE Publishing, 2016)
Major aortopulmonary collateral arteries are abnormal vascular structures that may be seen in cyanotic diseases that progress with reduced pulmonary flow. They occur rather rarely in the absence of cyanotic congenital heart disease. Presently described is the case of an infant who underwent patent ductus arteriosus (PDA) and major aortopulmonary collateral artery occlusion in a single session, without presence of cyanotic congenital heart disease. To the best of our knowledge, this is the first case of congenital aortopulmonary collateral artery to be reported in a symptomatic infant with PDA.